2(10-x)+8(10+3x)=x-8+3x

Simple and best practice solution for 2(10-x)+8(10+3x)=x-8+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(10-x)+8(10+3x)=x-8+3x equation:


Simplifying
2(10 + -1x) + 8(10 + 3x) = x + -8 + 3x
(10 * 2 + -1x * 2) + 8(10 + 3x) = x + -8 + 3x
(20 + -2x) + 8(10 + 3x) = x + -8 + 3x
20 + -2x + (10 * 8 + 3x * 8) = x + -8 + 3x
20 + -2x + (80 + 24x) = x + -8 + 3x

Reorder the terms:
20 + 80 + -2x + 24x = x + -8 + 3x

Combine like terms: 20 + 80 = 100
100 + -2x + 24x = x + -8 + 3x

Combine like terms: -2x + 24x = 22x
100 + 22x = x + -8 + 3x

Reorder the terms:
100 + 22x = -8 + x + 3x

Combine like terms: x + 3x = 4x
100 + 22x = -8 + 4x

Solving
100 + 22x = -8 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
100 + 22x + -4x = -8 + 4x + -4x

Combine like terms: 22x + -4x = 18x
100 + 18x = -8 + 4x + -4x

Combine like terms: 4x + -4x = 0
100 + 18x = -8 + 0
100 + 18x = -8

Add '-100' to each side of the equation.
100 + -100 + 18x = -8 + -100

Combine like terms: 100 + -100 = 0
0 + 18x = -8 + -100
18x = -8 + -100

Combine like terms: -8 + -100 = -108
18x = -108

Divide each side by '18'.
x = -6

Simplifying
x = -6

See similar equations:

| 3s+5s-6=34 | | 7b-4=17 | | 8e+6=10000 | | 50x-80y= | | 21=6+3v | | 8e+6= | | 2(4c-3)=42 | | 7[k-7]=2[11+k] | | (1n+2)(2n+5)=0 | | 14=2a-6 | | -5t^2+40t+60=0 | | x^2+2x^2-125=0 | | 4x^2-40x+45=0 | | 23x-12= | | 0.8x+20-4.5=5+x-0.9x | | 7a+5a=4(a-8)+12(a+9) | | 2(4x-1)+1=20 | | 2n-2=n-8 | | X^2+12x+y^2+4y=60 | | 7y+8=68 | | 6x=333334y | | 10x-7x=84 | | 7y+x=-20 | | 5h+7=3(2h-1) | | X+7y=-20 | | k/2+1=k/3-1 | | x+35+35=180 | | -8=y-6 | | 8(n-3)-(2-n)= | | 5[h+2]=3[j-1] | | 3x(X+1)-3x= | | -9+w=-7 |

Equations solver categories